Late Proterozoic-Paleozoic Tectonostratigraphic Development and Paleogeography of Brunovistulian Terrane and Comparison with Other Terranes at the SE Margins of Baltica-Laurussia - Kalvoda,J.; Melichar,R.; Babek,O.; Leichmann,J. (Journal of the Czech Geological Society, 2002)
There are close similarities between the Brunovistulian Terrane and the Istanbul Zone both in the Neoproterozoic and Paleozoic. The geological structure, lithology and geochronology of the Cadomian Brunovistulicum show a broad fit with the crystalline basement of the Istanbul Zone. Their Gondwana or Baltica affinity is still poorly constrained and remains a matter of discussion. The Vendian and Cambrian sequences recognized in the central Malopolska, Brunovistulian and Moesian terranes correlate well with the Seythian Platform. In the Istanbul Zone the presence of pre-Ordovician sedimentary sequences has not been confirmed and may only be anticipated. In Paleozoic the best fit was attained in the Devonian-Carboniferous. The sedimentary record in the Zonguldak and Istanbul terranes correlates closely to the Moravian Karst and Ludmirov facies development of the Brunovistulian Terrane. This correlation is reinforced by the good fit of the main Variscan deformation phases attributed in both the Brunovistulian Terrane and the Istanbul Zone to the late Viscan-early Namurian and Westphalian-Stephanian intervals. This supports, together with the paleobiogeographical data, the interpretation that the Istanbul and Zonguldak terranes can be regarded as counterparts to the Rhenohercynian and Subvariscan Zone in Central Europe. The Istanbul Zone was juxtaposed against the Sakarya Zone viewed as a part of the Armorican Terrane Assemblage.
Keywords: Brunovistulicum; Istanbul Zone; terranes; paleogeography; late Neoproterozoic; Paleozoic